RANCANG BANGUN WEBSITE DINAS PENDAPATAN DAERAH (DISPENDA) KABUPATEN KATINGAN - Karolita, Devi; Lestari, Ariesta; Septhapianus, Septhapianus (Universitas Palangka Raya, 2014)
Department of Local Revenue on Katingan Regency has a local system to handle tax, such asregistration, data entry, and tax calculating. That system can only be accessed by Department ofLocal Revenue on Katingan Regency. On the previous system, all those tasks are done manually.Taxpayers had to come to Department of Local Revenue to get the information needed. On theother side, Department of Local Revenue on Katingan Regency doesn’t have a profile website thatcan be used to accommodate the aspirations of community about tax.The proposed system is developed using PHP programming language and MySQL as DBMS.The system also developed using Waterfall Modelling method, which is consist of 5 steps: analysis,design, coding, testing, and maintenance.The Content Management System (CMS) concept which is applied in the website helps thewebsite administrator manages the website easily. The application of e-government in theproposed website is applied to level 2, namely information level and interaction level.